Nivoi primene veštačke inteligencije u sistemima za ljudske resurse - Ćormarković, Teodora; Dražeta, Lazar; Njeguš, Angelina (The European Journal of Applied Economics, 2022)
As human capital has become a vital asset in contemporary businesses, utilizing human resources exceeds HRM function towards strategic business partnership within organizations. The key enabling factor was global ICT development that changed functional roles and responsibilities within operating business models and introduced machine intelligence that increased organizational capabilities while reducing human involvement. The paper discusses the current state of AI applications in HRM systems. Emphasis is placed on clarifying technological features and goals, as well as the evolution of existing HRM systems. Furthermore, the paper provides the framework of AI application levels that serve as a foundation for understanding the current operational potential and provides useful evidence for the future development of HRM systems.